UJI KETAHANAN EMPAT VARIETAS PADI (Oryza sativa) DI SAMARINDA TERHADAP SERANGAN Leptocorisa acuta (Thunberg) (Hemiptera: Alydidae) - Rosfiansyah, Rosfiansyah; Romadhon, Rakhmat Akhiri; Sofian, Sofian (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2024)
The rice bug is a pest that is always an obstacle in rice cultivation because it sucks the rice grains and causes them to become empty. This study aims to determine the level of resistance and rice varieties that are most resistant to pest attack of pests and give the results of high yield. This research was conducted from April 2017 until August 2017, starting from planting to harvest, located at Bantuas Village, Palaran Subdistrict, Samarinda. This research used Randomized Block Design (RBD) with 4 Treatments and 6 replications. The treatments are: V1 (Cibogo Varieties), V2 (Ciherang Varieties), V3 (Inpari 30 Varieties), V4 (IR64 Varieties). The observed data were analyzed by fingerprint and followed by the smallest real difference test (BNT) at 5% level. The result of the research showed different attack level on 4 varieties of rice in each observation, the first observation of the highest attack was on ciherang varieties (V2), the second highest observation was found on cibogo variety (V1), the third highest observation was found in cibogo (V1) and varieties that give high yield of inpari 30 (V3).